From Empire to Nation : the rise to Self Assertion of Asian and African Peoples. - "Emerson, Rupert." (Calcutta, 1970)
The book is deal with the rise and self assertion of Asian and African peoples. The book also explain about nationalism and democracy.
Keywords: Political Science .